Effects of fiber and resistant starch in "Mangpis" cookies on changes in blood lipid profile in obese patients obesity - Masdayani Junita Napitupulu; Ahmad Syauqy; Nyoman Suci Widyastiti; Diana Nur Afifah; Etika Ratna Noer (AcTion: Aceh Nutrition Journal, 2024)
Abnormal lipid profiles can cause obesity-associated heart diseases. Increased total cholesterol, Low-Density Lipoprotein (LDL), triglyceride (TG), and High-Density Lipoprotein (HDL) levels are indicators of obesity. This study aimed to identify the dietary fiber and resistant starch in mangpis cookies and analyze the effects of mangpis cookies on reducing lipid profiles. This study used a pre-test and post-test  design to measure lipid profiles before and after eating mangpis. Mangpis cookies were prepared without wheat flour and replaced with 50% Bruguiera gymnorhiza mangrove flour and 50% banana flour. This experiment was conducted on 16 obese subjects. The sampling technique used was purposive. A decrease in the lipid profile was observed based on the results of blood tests before and after the consumption of mangpis cookies. The effect of the consumption of mangpis cookies on reducing lipid profiles was assessed using the Paired T-test and Wilcoxon test. The analysis results of the food fiber content and resistant starch contained in the mangpis cookies were 7,86 ± 004 and 6,65 ± 0,01 with p-value TG (p=0,001 and HDL (p=0,01). In conclusion, mangpis cookies were identified to contain 17,8% dietary fiber and 15% resistant starch, which could influence the lipid profile, especially TG levels.